2019
DOI: 10.1097/rhu.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Thrombophilic Arteritis

Abstract: Macular lymphocytic arteritis or lymphocytic thrombophilic arteritis (LTA) is a recently described cutaneous arteritis that is characterized by asymptomatic macules and patches of the extremities associated with lymphocytic arteritis at the deep dermal/subcuticular junction for which little information exists on demographics, evaluation, and management. There has been recent debate in the literature whether this disease is a new distinct entity, misdiagnosed cutaneous polyarteritis nodosa (cPAN), or a disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The term LTA was introduced as alternative nomenclature because these pathologic findings were seen in the absence of macules at presentation . A recent review has suggested that it does not belong on the spectrum of cPAN and systemic PAN due to its almost certain indolent course and lack of systemic symptoms, which is exhibited in our patient’s presentation. A recent review suggests the following criteria be considered in making the diagnosis of LTA: (i) presence of macules, papules, and/or patches that follow a benign course, (ii) histology demonstrating small‐medium vessel vasculitis with a predominantly lymphocytic infiltrate, and (iii) absence of signs or symptoms to suggest systemic vasculitis …”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The term LTA was introduced as alternative nomenclature because these pathologic findings were seen in the absence of macules at presentation . A recent review has suggested that it does not belong on the spectrum of cPAN and systemic PAN due to its almost certain indolent course and lack of systemic symptoms, which is exhibited in our patient’s presentation. A recent review suggests the following criteria be considered in making the diagnosis of LTA: (i) presence of macules, papules, and/or patches that follow a benign course, (ii) histology demonstrating small‐medium vessel vasculitis with a predominantly lymphocytic infiltrate, and (iii) absence of signs or symptoms to suggest systemic vasculitis …”
Section: Discussionmentioning
confidence: 61%
“…Given the patient’s lack of symptoms and associated pathologic findings, we made the diagnosis of lymphocytic thrombophilic arteritis (LTA). LTA typically presents in middle‐aged women as brown or erythematous hyperpigmented macules or livedoid patches on the lower extremities . Median duration of the clinical course is one year, but it has been reported to last up to 15 years .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been debate in the literature about whether macular arteritis represents an indolent nonnodular variant of cutaneous polyarteritis nodosa or a distinct entity. 4 , 15 , 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%